Tauhid sebagai Fondasi Kesehatan Mental Islami: Tinjauan Literatur atas Krisis Psikologis Modern - Dadan Firdaus; Mohamad Ihsan Kamaluddin (Nathiqiyyah, 2025)
This study explores the central role of tawḥīd (Islamic monotheism) as a foundational concept in shaping Islamic approaches to mental health, particularly in addressing the psychological crisis of the modern era. Using a qualitative literature review method, the research analyzes classical and contemporary sources in Islamic theology and psychology to identify the theological, psychological, and therapeutic dimensions of tawḥīd. The findings demonstrate that tawḥīd, as the doctrine of divine oneness, offers more than metaphysical truth; it provides an existential framework that supports emotional stability, spiritual resilience, and psychological well-being. The study highlights how the three dimensions of tawḥīd—rubūbiyyah (divine lordship), ulūhiyyah (divine worship), and asmāʾ wa ṣifāt (divine names and attributes)—contribute to reducing anxiety, instilling purpose, and protecting individuals from identity confusion and spiritual emptiness in the face of social comparison, digital overstimulation, and moral relativism. Moreover, the research emphasizes the practical implementation of tawḥīd through education, daʿwah, and tauhīd-based therapy. It calls for a systemic integration of tawḥīd into modern mental health strategies for Muslim communities. The study concludes that the internalization of tawḥīd is not only essential to religious faith but is also a transformative paradigm for restoring personal peace, meaning, and collective emotional health in a fragmented world.